Non-immunoglobulin E-mediated gastrointestinal food allergies in children with Down syndrome: An epidemiological study - Fumiko Okazaki, MD; Hiroyuki Wakiguchi, MD, PhD; Yuno Korenaga, MD; Mototsugu Shimokawa, PhD; Tsuyoshi Tanabe, MD, PhD; Ken Fukuda, MD, PhD; Masanari Hasegawa, MD, PhD; Miho Shimizu, MD, PhD; Reiji Hirano, MD, PhD; Tadashi Moriwake, MD, PhD; Mai Kawamura, MD; Hiroshi Tateishi, MD, PhD; et al. (World Allergy Organization Journal)
Background: Non-immunoglobulin E-mediated gastrointestinal food allergies (non-IgE-GI-FAs) in children with Down syndrome (DS) tend to be more severe, with some children presenting with sepsis-like symptoms. However, the epidemiology of this condition remains unknown. This study aimed to investigate the prevalence rate and clinical characteristics of non-IgE-GI-FAs in children with DS. Methods: This study included 115 children with non-IgE-GI-FAs diagnosed at 13 hospitals in Yamaguchi Prefecture, Japan, between January 1, 2011, and December 31, 2020. The children were classified into DS and non-DS groups, and their clinical characteristics were retrospectively compared. Results: Among the 115 children with non-IgE-GI-FAs, 7 and 108 were included in the DS and non-DS groups, respectively. During the study period, 184 children with DS were born in Yamaguchi prefecture, and 7 developed non-IgE-GI-FAs. In this study, the prevalence rate of non-IgE-GI-FAs was 3.8% (7/184) in children with DS and 0.11% (108/98,989) in children without DS. No significant differences were observed in causative foods, age at onset, age at diagnosis, or age at confirmed clinical remission between the 2 groups. Most children in both groups experienced vomiting and diarrhea, but none had hypothermia. Sepsis-like symptoms, such as lethargy (71.4% vs. 24.1%, P = 0.0150), hypotension (42.9% vs. 0.9%, P = 0.0006), and fever (57.1% and 8.3%, P = 0.0030), were significantly more common in the DS group than in the non-DS group. Conclusions: The prevalence rate of non-IgE-GI-FAs was 3.8% in children with DS and 0.11% in children without DS. Non-IgE-GI-FAs in children with DS were significantly more severe than those in children without DS. Non-IgE-GI-FAs should be considered a differential diagnosis when sepsis-like symptoms are observed in children with DS.